EFFECT OF NICKEL PULSED ELECTRODEPOSITION PARAMETERS ON DEPOSIT MICROSTRUCTURE AND CORROTION RATE AISI 410 - Agnes Stephani; Soesaptri Oediyani; Yulinda Lestari; Efendi Mabruri (Pusbindiklat - LIPI, 2018)
Nickel pulse electrodeposition is one of the coating methods that used to increase the corrosion resistance and improve the mechanical properties. In this study, nickel was used as the anode and martensitic stainless steel 410 was used as the cathode. The solution used in the method of nickel pulse electrodeposition include nickel sulfate, nickel chloride, and boric acid. Pulse electrodeposition parameters are variation of duty cycle of 70, 80, 90% and frequency variations valued at 0.1, 1, 10, and 20 kHz. Temperatures used in research nickel pulse electrodeposition at 50 ° C, with a current density of 15 A / dm² and 18 minutes. The Scanning Electron Microscopy analysis determine the microstructure and grain size changes after a nickel pulse electrodeposition. The polarization test determine optimum rate of corrosion when 90 % duty cycle and 20 kHz frequency.